Struktur Sosial Masyarakat Bima Pada Masa Kepemimpinan Sultan Muhammad Salahuddin Tahun 1915-1951 - Muhammad Al Qautsar Pratama; Cecep Somantri (IAIN Syekh Nurjati Cirebon, 2019)
AbstractBima’s society has its own styles and social structures in the history’s journey and it keeps changing. Social structure in Bima is not apart from the influence of their current goverment. In the goverment of Sultan Muhammad Salahuddin as the latest sultan in 1915 – 1951, he gave a lot of contributions to social and spiritual of Bima’s society. This study concerns about the development of Bima’s society that describes about the social status and also the symbols. This study also describes about the social life in every status and the policies of Sultan Muhammad Salahuddin that influence the social paradigm of Bima. Keywords: Social structures, Bima’s society, Sultan Muhammad Salahuddin